Pragmatic Considerations in Incorporating Stakeholder Engagement Into a Palliative Care Transitions Study - de Forcrand, Claire (Med Care, 2021)
Stakeholder involvement in health care research has been shown to improve research development, processes, and dissemination. The literature is developing on stakeholder engagement methods and preliminarily validated tools for evaluating stakeholder level of engagement have been proposed for specific stakeholder groups and settings. OBJECTIVES: This paper describes the methodology for engaging a Study Advisory Committee (SAC) in research and reports on the use of a stakeholder engagement survey for measuring level of engagement. METHODS: Stakeholders with previous research connections were recruited to the SAC during the planning process for a multicenter randomized control clinical trial, which is ongoing at the time of this writing. All SAC meetings undergo qualitative analysis, while the Stakeholder Engagement Survey instrument developed by the Patient-Centered Outcomes Research Institute (PCORI) is distributed annually for quantitative evaluation. RESULTS: The trial’s SAC is composed of 18 members from 3 stakeholder groups: patients and their caregivers; patient advocacy organizations; and health care payers. After an initial in-person meeting, the SAC meets quarterly by telephone and annually in-person. The SAC monitors research progress and provides feedback on all study processes. The stakeholder engagement survey reveals improved engagement over time as well as continued challenges. CONCLUSIONS: Stakeholder engagement in the research process has meaningfully contributed to the study design, patient recruitment, and preliminary analysis of findings.